Enzymatic surface hydrolysis of poly(ethylene furanoate) thin films of various crystallinities. Issue 22 (2nd November 2017) - Weinberger, S.; Haernvall, K.; Scaini, D.; Ghazaryan, G.; Zumstein, M. T.; Sander, M.; Pellis, A.; Guebitz, G. M.
Abstract : This work reports on the successful production of poly(ethylene furanoate) (PEF) thin films and a comparison of the enzymatic hydrolysis of PEF and poly(ethylene terephthalate) (PET) films with three different crystallinities (0, 10 and 20%). Abstract : This work reports on the successful production of poly(ethylene furanoate) (PEF) thin films and a comparison of the enzymatic hydrolysis of PEF and poly(ethylene terephthalate) (PET) films with three different crystallinities (0, 10 and 20%). The data suggest that the PEF films are enzymatically hydrolyzed 1.7 times faster than the commonly investigated PET films. QCM-D and SEM/AFM analyses fully confirm the observed reaction trend. The results also show a negative dependence of the hydrolysis rates with the increasing of the film crystallinity.